Social Support in the Workplace, Praying for Others, and Job Satisfaction - Jung, Jong Hyun (Review of religious research, 2025)
This research note aims to examine how social support in the workplace is associated with job satisfaction in Singapore. More importantly, it evaluates how the frequency of praying for others moderates this association. Using data from the Work, Religion, and Health survey (n?=?508), a nationwide study of workers in Singapore collected in 2021, our regression analyses show that receiving social support in the workplace is positively associated with job satisfaction. In addition, the positive association between receiving social support in workplace and job satisfaction is stronger for individuals who pray for others more frequently. The results suggest that those who engage in prayer on behalf of others more frequently obtain greater benefits from workplace social support in the form of job satisfaction. These observations indicate that private religious behavior may act as a key relational resource that promotes worker well-being.